Lead poisoning prevention: A community-based participatory research program in Mississippi (IMC Journal of Medical Science, 2021)
Background and objectives: Lead poisoning is a preventable environmental health hazard. Although the prevalence of lead poisoning is declining, the rates are disproportionately high in selected communities. This community-based participatory research (CBPR) program aimed to enhance people’s awareness on lead poisoning prevention through community outreach and educational interventions in Mississippi.Methods: Secondary data of 42,372 children obtained from the Mississippi State Department of Health were analyzed to identify the most affected communities in Mississippi. Community-based outreach and education activities were carried out in the most affected areas to increase population awareness on lead poisonig prevention.Results: Hands-on training was offered to 25 participants at homebuilding retail stores. Of them, 23 (92%) reported the hands-on training was very useful or useful. Among 91 home-buyers and rental home owners who attended workshops offered by the Neighborhood Association, 90% mentioned that the training was useful or very useful. An online visual training was given to 220 realtors, and 75 inspectors, contractors, and Do-It-Yourself (DIY) workers. At posttest, 59.4%, 67.9%, 65.1% of the realtors, inspectors, contractors and DIY workers (n = 295) identified soil, car batteries and paint as sources of lead in the environment, respectively. A total of 62.3%, 48.1% and 58.5%, at posttest, identified three complications - behavioral, physical and psychological, respectively. The mean posttest score was significantly higher than the pretest scores (7.47 ± 2.07 vs. 6.60 ± 1.68, p = 0.04, respectively).Conclusion: These outreach activities were successful in improving the knowledge of the community people on lead poisoning prevention.Ibrahim Med. Coll. J. 2021; 15(1): 16-25